O uso de técnicas de realidade virtual e aumentada na simulação de prótese de membros superiores - Nogueira, Kenedy Lopes (2007)
In this days with a great technological development of sciences in general, the humanity possesses more resources to promote a long and healthful life. New techniques are created to increase the life quality, however still many areas need research, one of these are the recovery of amputated patients to prostheses. The technology of prostheses construction is in constant research but the patients adaptation to these prostheses is slow and tiring. In this way this dissertation has as objective to investigate computational techniques that support simulations and training of prostheses through the interaction with a graphical interface that will stimulates patients to the use of prostheses For this the use of Virtual Reality (VR) and Augmented Reality (AR) techniques, valued for the power of immersion, interaction and navigation. Initially, it has accomplished a review of the main characteristics of the classification systems and simulation of upper limbs movements. Basing in these studies, the limitations of the existing systems were determined in terms of the virtual environments exhibition. A system was proposed to possible the users to overcome the difficulties of there deficiency. With that, the integration of the acquisition systems was obtained through a 3D graphical interface with high interaction level. With the members movements classification and the biomedical signal analysis, such as Electromyography, signal proceeding from the muscular contractions very used in the biomechanics prostheses control.